2011
DOI: 10.1371/journal.pone.0028282
|View full text |Cite
|
Sign up to set email alerts
|

Progressive, Transgenerational Changes in Offspring Phenotype and Epigenotype following Nutritional Transition

Abstract: Induction of altered phenotypes during development in response to environmental input involves epigenetic changes. Phenotypic traits can be passed between generations by a variety of mechanisms, including direct transmission of epigenetic states or by induction of epigenetic marks de novo in each generation. To distinguish between these possibilities we measured epigenetic marks over four generations in rats exposed to a sustained environmental challenge. Dietary energy was increased by 25% at conception in F0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 36 publications
4
91
0
3
Order By: Relevance
“…Four of these miRNAs (hsa-miR-146b-5p, hsamiR-509-5p, hsa-miR-519d and hsa-miR-652) have already been shown to be altered in the testes, seminal plasma and/or semen environmental toxins and factors) can induce harmful phenotypes in the descendants of exposed individuals. [6][7][8][9][10][11][12][13][14] Although the mechanisms underlying transmission of environmentallyinduced phenotypes through generations are not well understood, epigenetic changes within the germ line appear to play a central role. The association of DNA methylation with environmental exposures and heritable phenotypes has been widely established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four of these miRNAs (hsa-miR-146b-5p, hsamiR-509-5p, hsa-miR-519d and hsa-miR-652) have already been shown to be altered in the testes, seminal plasma and/or semen environmental toxins and factors) can induce harmful phenotypes in the descendants of exposed individuals. [6][7][8][9][10][11][12][13][14] Although the mechanisms underlying transmission of environmentallyinduced phenotypes through generations are not well understood, epigenetic changes within the germ line appear to play a central role. The association of DNA methylation with environmental exposures and heritable phenotypes has been widely established.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Such multigenerational toxicity has been observed following exposure to other environmental chemicals and environmental factors such as nutrition and stress. [8][9][10][11][12][13][14] Epidemiological studies suggest that this phenomenon may also occur in human populations. [15][16][17][18][19] recent work has suggested that environmental chemicals, including those contained in cigarette smoke, can have adverse effects on the exposed individuals as well as their future progeny.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Data memperlihatkan bahwa regulasi metabolism energi selama kehamilan pada satu generasi dipengaruhi oleh fenotipe maternal generasi sebelumnya dan lingkungan selama kehamilan. 19 Asupan protein dalam penelitian ini tidak berbeda bermakna untuk kedua kelompok IMT tinggi dan rendah ada awal kehamilan; asupan protein ini juga sudah mencukupi kebutuhan menurut berat badan subjek (0,93 g/kgBB), yaitu 0,8-1 g/kgBB. Kecukupan energi dan protein tersebut didasarkan berat badan pada awal kehamilan.…”
Section: Pembahasanunclassified
“…Epigenetic changes can be induced by DNA damage [O'Hagan et al, 2008;Tabish et al, 2012] but also by the environment, thus providing a connection between the outer world and DNA, that is, the genetic library where all possible repertoires of molecular responses are stored. For example, food can alter the epigenetics of rats on different diets [Burdge et al, 2011] and changes in DNA methylation may occur as a result of low dietary levels of folate, methionine, or selenium, which can have profound clinical consequences such as neural tube defects, cancer and atherosclerosis [Friso and Choi, 2002;Ulrey et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…of rats on different diets [Burdge et al, 2011] and changes in DNA methylation may occur as a result of low dietary levels of folate, methionine, or selenium, which can have profound clinical consequences such as neural tube defects, cancer and atherosclerosis [Friso and Choi, 2002;Ulrey et al, 2005].…”
mentioning
confidence: 99%